A novel insight into the cardiotoxicity of antineoplastic drug doxorubicin - Heger, Zbynek; Cernei, Natalia; Kudr, Jiri; Gumulec, Jaromir; Blazkova, Iva; Zitka, Ondrej; Eckschlager, Tomas; Stiborova, Marie; Adam, Vojtech; Kizek, Rene (International journal of molecular sciences, 2013)
Doxorubicin is a commonly used antineoplastic agent in the treatment of many types of cancer. Little is known about the interactions of doxorubicin with cardiac biomolecules. Serious cardiotoxicity including dilated cardiomyopathy often resulting in a fatal congestive heart failure may occur as a consequence of chemotherapy with doxorubicin. The purpose of this study was to determine the effect of exposure to doxorubicin on the changes in major amino acids in tissue of cardiac muscle (proline, taurine, glutamic acid, arginine, aspartic acid, leucine, glycine, valine, alanine, isoleucine, threonine, lysine and serine). An in vitro interaction study was performed as a comparison of amino acid profiles in heart tissue before and after application of doxorubicin. We found that doxorubicin directly influences myocardial amino acid representation even at low concentrations. In addition, we performed an interaction study that resulted in the determination of breaking points for each of analyzed amino acids. Lysine, arginine, β-alanine, valine and serine were determined as the most sensitive amino acids. Additionally we compared amino acid profiles of myocardium before and after exposure to doxorubicin. The amount of amino acids after interaction with doxorubicin was significantly reduced (p = 0.05). This fact points at an ability of doxorubicin to induce changes in quantitative composition of amino acids in myocardium. Moreover, this confirms that the interactions between doxorubicin and amino acids may act as another factor most likely responsible for adverse effects of doxorubicin on myocardium.
Keywords: Drug-Related Side Effects and Adverse Reactions; Humans; Chickens; chromatografie iontoměničová; doxorubicin; Antineoplastic Agents; Doxorubicin; lidé; nežádoucí účinky léčiv; zvířata; aminokyseliny; Amino Acids; kur domácí; Chromatography, Ion Exchange; Heart; Neoplasms; protinádorové látky; nádory; myokard; Animals; Myocardium; srdce